High IL-6 expression in the tumor microenvironment is associated with poor prognosis of patients with extranodal natural / killer T-cell lymphoma (ENKTL). Issue 1 (2nd January 2021) - Rong, Qixiang; Gao, Yan; Cai, Qichun; Wang, Xiaoxiao; Bai, Bing; Ping, Liqin; He, Haixia; Rao, Huilan; Zhang, Yujing; Li, Zhiming; Cai, Qingqing; Jiang, Wenqi; et al.
ABSTRACT: Objectives : Extranodal natural/killer T-cell lymphoma (ENKTL) is a rare subtype of T cell non-Hodgkin's lymphoma. Current clinical prognostic models for ENKTL still have their limitations. Validated prognostic models for ENKTL have not yet been established. Methods : Tumor microenvironment IL-6 was measured by immunohistochemistry in 78 ENKTL patients. Results : Patients with negative IL-6 expression in the tumor microenvironment have a longer PFS (56.0 months vs. 25.6 months, p < 0.001) and OS (96.0 months vs. 43.3 months, p < 0.001). In the multivariate analysis, tumor microenvironment IL-6 [p = 0.048, HR = 1.76(1.00–3.08)] and extranodal involvement [p = 0.001, HR = 2.69(1.50–4.82)] were independent prognostic factors for PFS. Tumor microenvironment IL-6 [p = 0.033, HR = 2.69 (1.08–6.67)], Ann Arbor stage [p = 0.002, HR = 2.77 (1.47–5.23)] and B symptom [p = 0.027, HR = 2.02 (1.08–3.78)] were independent prognostic factors for OS. Expert opinion : A high IL-6 expression was related to poor survival, which may be a valuable biomarker for prognostic evaluation at baseline in ENKTL. These results showed that anti-IL-6R may be a potential targeted therapy for the treatment of advanced or relapsed ENKTL.